FACTORS MAKING UNDERGRADUATE STUDENTS TO BECOME A PROCRASTINATOR (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Procrastination has become a big problem in the majority of the world’s population’s behavior regardless of their culture or professions. As a result, people tend to end up not being able to meet the deadlines and experience negative  psychological states such as stress or depression. This article mainly focuses on the reasons of undergraduate students for postponing their academic responsibilities and gives some practical recommendations to get rid of this behavior.